2011
DOI: 10.2478/s11756-011-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of humic substances on germination and early growth of Lamb’s Quarters (Chenopodium album agg.)

Abstract: In order to understand the biological activity of humic substances (HS), the effect of four humic acids (HA) and one fulvic acid (FA) on seed germination and early growth of cosmopolitan weed Chenopodium album agg. were tested. Humic substances of diverse origin were used, namely purified commercial HA, HA isolated from lignite, cambisol and podzol, and FA from mountain spruce forest soil. Data processing by two-way ANOVA has shown that type of the tested substances was a more important factor on seed developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The findings of this experiment suggest that the highest germination percentage for varieties belongs to G1 and that, when they were exposed to germination promoters, HS achieved a higher germination for both G1 and G2 (Table 2 and 3). These results match the findings of authors such as Rodrigues et al (2017) and Šerá and Novák (2011), who assessed the effect of treating maize seeds with a humic acid-based commercial product and found that humic acid promotes a greater growth of seedlings, in addition to greater dry mass of maize sprouts. These results have a positive influence on the emergence rate index, up to doses of 158 mL 100 kg 1 seeds.…”
Section: Germination Percentagesupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this experiment suggest that the highest germination percentage for varieties belongs to G1 and that, when they were exposed to germination promoters, HS achieved a higher germination for both G1 and G2 (Table 2 and 3). These results match the findings of authors such as Rodrigues et al (2017) and Šerá and Novák (2011), who assessed the effect of treating maize seeds with a humic acid-based commercial product and found that humic acid promotes a greater growth of seedlings, in addition to greater dry mass of maize sprouts. These results have a positive influence on the emergence rate index, up to doses of 158 mL 100 kg 1 seeds.…”
Section: Germination Percentagesupporting
confidence: 89%
“…These results have a positive influence on the emergence rate index, up to doses of 158 mL 100 kg 1 seeds. For their part, Šerá and Novák (2011) used seeds of Lamb's Quarters (Chenopodium album agg.) and determined that the main differences in germination and length of sprouts occurred during the first days of the experiment.…”
Section: Germination Percentagementioning
confidence: 99%
“…All the experiments were performed in duplicate. Germination tests were not performed, since they have been already studied for the humic acid extracted from South-Moravian lignite by Šerá and Novák (2011), when germination stimulating effects have been proven for this humic acid even on non-cultural plant of Lamb’s Quarters ( Chenopodium album ). Similarly, the stress tests on the plants have not been applied, since the plants seemed to present uniform leave numbers, lengths and areas and these would be far beyond the scope of this work.
Figure 1 Placing the germs in testing polystyrene containers, with 30 germs per container and each 5 of them placed in a marked position on a floating styrofoam bed to be observed later for root length and division.
…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Gupta and Gupta (2011) reported a similar effect on okra seeds germination when sowing was performed 6 to 18 h after treatment with anaerobically digested poultry manure. This negative effect has been explained by the existence of humic acids in digested manure that formed during anaerobic digestion (Bacilio et al 2003;Šerá and Novák 2011). In another study, Kaparaju et al (2012) reported that anaerobically digested orange waste have a toxic effect on seeds germination of Chinese cabbage and they referred this toxicity to ammonia and organic acids in the digestate.…”
Section: Seedlings Dry Weightmentioning
confidence: 99%